Populism - Lars Frisell (Sveriges Riksbank, 2004)
In their pursuit of being elected, politicians might not provide their constituents with independent viewpoints, but just try to outguess popular opinion. Although rational voters see through such populism, candidates can not resist resorting to it when the spoils of office are too large. For an intermediate parameter range, both populism and its opposite, candor, can be sustained as equilibria. This means that the publics trust or distrust in politicians may be self-fulfilling prophecies. Importantly, the more informed politicians are about public opinion, the more likely it is that populist behavior can be avoided.
Keywords: D72; D82; 330; popular opinion; electoral competition; candidate motivation; pandering; political trust